738 Role of non-coding RNA uc.194 and uc.443+A in the intrastent restenosis. (8th December 2021) - Boccuto, Fabiola; Tammè, Laura; Iaconetti, Claudio; Sabatino, Jolanda; Polimeni, Alberto; Sorrentino, Sabato; Carbone, Andrea; Gareri, Clarice; Mancuso, Teresa; De Rosa, Salvatore; Indolfi, Ciro
Abstract: Aims: Vascular smooth muscle cells (VSMCs) play a key role in the vessel wall, being active partaker in vascular remodelling and influencing multiple pathophysiological phenomena, such as progression of atherosclerosis, in-stent restenosis and vascular reactivity. Recently antisense oligonucleotides have shown promising results as a therapeutic option. The aim of this study was to analyse the expression profile and function of T-UCRs in vascular smooth muscle cells (VSMCs)—both in vitro and in vivo—and to evaluate the effects of their inhibition by the use of specific antisense oligonucleotides. Methods: After obtaining cell cultures of vascular smooth muscle cells, we modified their phenotype varying growth conditions. A microarray and qRT-PCR expression profile analysis and a cell cycle analysis with cell proliferation/apoptosis/migration assay were performed. In vivo studies were performed on rat carotids after cell damage and administration of specific antisense oligonucleotides. Results: There were significant differences in the expression of T-UCRs in VSMCs with a proliferating and quiescent phenotype. In particular, 5 T-UCRs were found to be upregulated in VSMCs. These types of cells were subsequently transfected with specific antisense oligonucleotides obtaining a reduction in their proliferative activity in particular with the inhibition of the T-UCRs uc.194 and uc.443 + A. MiR-10A and miR-34b-5p were identified with complementary sequences respectively to uc.194 and uc.443 + A. The increase of these miRs following the inhibition of the T-UCRs were closely related to the inhibition of the proliferative signals of VSMCs. Similarly, the same results were obtained in vivo. Conclusions: The expression levels of non-coding RNAs uc.194 and uc. 443 + A increase in proliferating smooth muscle cells in vitro and in the vascular wall following damage, suggesting an important role of these molecules in the phenomenon of intra-stent restenosis. Through the inhibition of uc.194 and uc.443 + A using an antisense strategy, we demonstrated a reduction in cell proliferation and migration processes and, consequently, in the formation of neointima. A possible relationship was also highlighted between the aforementioned non-coding RNAs and some micro-RNAs (miR-10A and miR-34b-5p), negative regulators of the proliferative phenotype of VSMCs. The inhibition of the analysed T-UCRs would allow the maintenance of the contractile phenotype thanks to the activity of the miRs analysed in this study. Our results might pave the way for the identification of new therapeutic targets in order to prevent and reduce the incidence of intra-stent restenosis.